Aiding early clinical drug development by elucidation of the relationship between tumor growth inhibition and survival in relapsed/refractory multiple myeloma patients. Issue 3 (2nd June 2022) - Cheng, Yiming; Hong, Kevin; Chen, Nianhang; Yu, Xin; Peluso, Teresa; Zhou, Simon; Li, Yan
Abstract: Early prognosis of clinical efficacy is an urgent need for oncology drug development. Herein, we systemically examined the quantitative approach of tumor growth inhibition (TGI) and survival modeling in the space of relapsed and refractory multiple myeloma (MM), aiming to provide insights into clinical drug development. Longitudinal serum M‐protein and progression‐free survival (PFS) data from three phase III studies ( N = 1367) across six treatment regimens and different patient populations were leveraged. The TGI model successfully described the longitudinal M‐protein data in patients with MM. The tumor inhibition and growth parameters were found to vary as per each study, likely due to the patient population and treatment regimen difference. Based on a parametric time‐to‐event model for PFS, M‐protein reduction at week 4 was identified as a significant prognostic factor for PFS across the three studies. Other factors, including Eastern Cooperative Oncology Group performance status, prior anti‐myeloma therapeutics, and baseline serum ß2‐microglobulin level, were correlated with PFS as well. In conclusion, patient disease characteristics (i.e., baseline tumor burden and treatment lines) were important determinants of tumor inhibition and PFS in MM patients. M‐protein change at week 4 was an early prognostic biomarker for PFS.